2020
DOI: 10.3390/cells9102295
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Pregnane X Receptor and Breast Cancer Growth and Progression

Abstract: Pregnane X receptor (PXR, NR1I2) is a member of the ligand-activated nuclear receptor superfamily. This receptor is promiscuous in its activation profile and is responsive to a broad array of both endobiotic and xenobiotic ligands. PXR is involved in pivotal cellular detoxification processes to include the regulation of genes that encode key drug-metabolizing cytochrome-P450 enzymes, oxidative stress response, as well as enzymes that drive steroid and bile acid metabolism. While PXR clearly has important regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…It increased the BAX p53; caspase 3 and 9; while reducing the bcl-2. In addition, Creamer et al, (2020) literally found the pregnane X receptor (PXR, NR1I2) role in the breast tissue. The activation of PXR has the main function in apoptosis, and develops in acquired resistance to chemotherapeutic substances.…”
Section: Discussionmentioning
confidence: 99%
“…It increased the BAX p53; caspase 3 and 9; while reducing the bcl-2. In addition, Creamer et al, (2020) literally found the pregnane X receptor (PXR, NR1I2) role in the breast tissue. The activation of PXR has the main function in apoptosis, and develops in acquired resistance to chemotherapeutic substances.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear receptors such as farnesoid X receptor (FXR), constitutive androstane receptor (CAR), peroxisome proliferator-activated receptor alpha (PPARα), liver X receptor (LXR), and androgen receptor, are candidates for the control of PXR expression. Additionally, possible coactivators that help the trafficking are steroid receptor coactivators (SRCs) 1, 2, and 3, peroxisome proliferator activated receptor gamma coactivator 1-alpha (PGC-1α), forkhead box O 1 transcription factor (FOXO1), protein arginine methyltransferase (PRMT), and p300 [61,62]. Furthermore, PXR may undergo epigenetic and post-translational modifications that affect its activity, so it may be selectively activated in some tumors [63].…”
Section: Discussionmentioning
confidence: 99%
“…While in mesenteric arteries, vasodilation was induced by the PXR agonist progesterone metabolite, probably via the induction of CYP enzymes. Furthermore, rifaximin which is a gut-specific human PXR ligand, is not effective for rodents; while pregnenolone-16 alpha carbonitrile (PCN) functions as a rodent-specific ligand (158)(159)(160)(161).…”
Section: Pregnane X Receptor (Pxr)mentioning
confidence: 99%